19.0k views
1 vote
-2(3x+1)+4=17 (Number only for your answer) *
Your answer

User Idchi
by
5.1k points

2 Answers

5 votes

Answer:x= -5/2

Step-by-step explanation: −2(3x+1)+4=17

(−2)(3x)+(−2)(1)+4=17(Distribute)

−6x+−2+4=17 (−6x)+(−2+4)=17(Combine Like Terms)

−6x+2=17

−6x+2=17

−6x+2−2=17−2

−6x=15

−6x/−6

=

15/−6

x=−5/2

User Brendan Falkowski
by
5.1k points
3 votes

Answer:

x= -5/2 (-2.5)

-2(3x+1)=17-4

-2(3x + 1) = 13

3x + 1 = 13/23x = -13/2 - 1

3x=-15/2

x=15/2/3

x=15/2x3

x=-15/6

x=-5/2

User Zakiya
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.